Females are sensitive to unpleasant human emotions regardless of the emotional context of photographs. (9th June 2017) - Kato, Ryousuke; Takeda, Yuji
Highlights: Females are sensitive to the depicted person's emotional state. We examined the effects of congruency between the valences of face and background. The late positive potential (LPP) was estimated as an index of emotional response. In females, unpleasant faces elicited larger LPP regardless of background contexts. Females are sensitive to human emotions regardless of the emotional contexts. Abstract: Previous studies have demonstrated that females exhibit higher sensitivity than males to the emotional state of a person in a photograph. The present study examined whether such females' sensitivity to human emotions could be observed even when the background emotional contexts were incongruent with facial expressions. The late positive potential (LPP) was measured while 19-female and 15-male participants viewed a photograph of a face with varied emotional expressions (pleasant, neutral, or unpleasant) superimposed on a background photograph with varied valences (pleasant, neutral, or unpleasant). The results showed that unpleasant background photographs elicited a larger LPP compared to pleasant and neutral background photographs in both female and male participants. In contrast, a larger LPP for the unpleasant face photographs was observed only in female participants. Furthermore, the effect of face photographs did not interact with the effect of background photographs. These results suggest that females are sensitive to human emotions regardless of the emotional context.